The Evolution and Everyday Practice of Collective Patient Involvement in Europe An Examination of Policy Processes, Motivations, and Implementations in Four Countries - Haarmann, Alexander (Springer International Publishing, 2018)
This timely study analyzes social, economic, political, provider, and patient factors shaping collective patient involvement in European health care from the postwar period to the present day. Examining representative countries England, the Netherlands, Germany, and Sweden, it documents the roles of providers and legislatures in facilitating consumer involvement, and the varied forms of patient input into hospital operations. These findings are compared and contrasted against the intent and ideals behind patient involvement to assess the effectiveness of implementation policy, strengths and drawbacks of patient participation, and patient satisfaction and outcomes. The book's conclusions identify emerging forms of patient participation and predict the impact of health policy on the future of European collective patient involvement. Included in the coverage: · Patient involvement: who, what for, and in what way? · The Netherlands: the legislative process to collective patient involvement · England: formal means of public involvement-a continuous story of discontinuity · Germany: Joint Federal Committee-the "Little Legislator" · Sweden: reasons for a late emergence of patient involvement · Lessons to be learned from implementing patient involvement The Evolution and Everyday Practice of Collective Patient Involvement in Europe will interest and inspire scholars and researchers in diverse fields, including social policy, sociology, political sciences, and nursing studies, as well as patient organizations, policymakers, and healthcare providers. .